Trends in mortality from external causes in the Republic of Seychelles between 1989 and 2018 - Abio, Anne; Bovet, Pascal; Didon, Joachim; Bärnighausen, Till; Shaikh, Masood Ali; Posti, Jussi P.; Wilson, Michael (Scientific reports, 2020)
Data on injury-related mortality are scarce in the African region. Mortality from external causes in the Seychelles was assessed, where all deaths are medically certified and the population is regularly enumerated. The four fields for underlying causes of death recorded were reviewed in the national vital statistics register. The age-standardised mortality rates were estimated (per 100,000 person-years) from external causes in 1989-1998, 1999-2008, and 2009-2018. Mortality rates per 100,000 person-years from external causes were 4-5 times higher among males than females, and decreased among males over the three 10-year periods (127.5, 101.4, 97.1) but not among females (26.9, 23.1, 26.9). The contribution of external causes to total mortality did not change markedly over time (males 11.6%, females 4.3% in 1989-2018). Apart from external deaths from undetermined causes (males 14.6, females 2.4) and “other unintentional injuries” (males 14.1, females 8.0), the leading external causes of death in 2009-2018 were drowning (25.9), road traffic injuries (18.0) and suicide (10.4) among males; and road traffic injuries (4.6), drowning (3.4) and poisoning (2.6) among females. Mortality from broad categories of external causes did not change consistently over time but rates of road traffic injuries increased among males. External causes contributed approximately 1 in 10 deaths among males and 1 in 20 among females, with no marked change in cause-specific rates over time, except for road traffic injuries. These findings emphasise the need for programs and policies in various sectors to address this large, but mostly avoidable health burden.